Molecular Profiling Reclassifies Adult Astroblastoma into Known and Clinically Distinct Tumor Entities with Frequent Mitogen‐Activated Protein Kinase Pathway Alterations. (25th July 2019) - Boisseau, William; Euskirchen, Philipp; Mokhtari, Karima; Dehais, Caroline; Touat, Mehdi; Hoang‐Xuan, Khê; Sanson, Marc; Capelle, Laurent; Nouet, Aurélien; Karachi, Carine; Bielle, Franck; Guégan, Justine; et al.
Abstract: Background: Astroblastoma (ABM) is a rare glial brain tumor. Recurrent meningioma 1 (MN1) alterations have been recently identified in most pediatric cases. Adolescent and adult cases, however, remain molecularly poorly defined. Materials and Methods: We performed clinical and molecular characterization of a retrospective cohort of 14 adult and 1 adolescent ABM. Results: Strikingly, we found that MN1 fusions are a rare event in this age group (1/15). Using methylation profiling and targeted sequencing, most cases were reclassified as either pleomorphic xanthoastrocytomas (PXA)‐like or high‐grade glioma (HGG)‐like. PXA‐like ABM show BRAF mutation (6/7 with V600E mutation and 1/7 with G466E mutation) and CD34 expression. Conversely, HGG‐like ABM harbored specific alterations of diffuse midline glioma (2/5) or glioblastoma (GBM; 3/5). These latter patients showed an unfavorable clinical course with significantly shorter overall survival ( p = .021). Mitogen‐activated protein kinase pathway alterations (including FGFR fusion, BRAF and NF1 mutations) were present in 10 of 15 patients and overrepresented in the HGG‐like group (3/5) compared with previously reported prevalence of these alterations in GBM and diffuse midline glioma. Conclusion: We suggest that gliomas with astroblastic features include a variety of molecularly sharply defined entities. Adult ABM harboring molecular features of PXA and HGG should be reclassified. Central nervous system high‐grade neuroepithelial tumors with MN1 alterations and histology of ABM appear to be uncommon in adults. Astroblastic morphology in adults should thus prompt thorough molecular investigation aiming at a clear histomolecular diagnosis and identifying actionable drug targets, especially in the mitogen‐activated protein kinase pathway. Implications for Practice: Astroblastoma (ABM) remains a poorly defined and controversial entity. Although meningioma 1 alterations seem to define a large subset of pediatric cases, adult cases remain molecularly poorly defined. This comprehensive molecular characterization of 1 adolescent and 14 adult ABM revealed that adult ABM histology comprises several molecularly defined entities, which explains clinical diversity and identifies actionable targets. Namely, pleomorphic xanthoastrocytoma‐like ABM cases show a favorable prognosis whereas high‐grade glioma (glioblastoma and diffuse midline gliome)‐like ABM show significantly worse clinical courses. These results call for in‐depth molecular analysis of adult gliomas with astroblastic features for diagnostic and therapeutic purposes. Abstract : Astroblastoma is a rare central nervous system tumor. This article reports on the common clinical and molecular features of astroblastoma in a cohort of 14 adults and one adolescent.